Electricity Load Forecasting in East Kalimantan on Religious Holidays Using SARIMA - Hasanah, Primadina; Alvionita Sari, Chindy; Ali Wira Dinata, Syalam (Universitas Negeri Padang, 2023)
The availability of electrical energy is one of the main focus in energy security in East Kalimantan. Power outages often occur in East Kalimantan both in weekdays and holidays. Some previous research had conducted to estimate the electricity demand during certain years. However, there are some particular events which are interesting to be carried out. For example, the electricity demands on holiday events such as the religious holidays which are important moment among Indonesian. This research was conducted to find the best model to predict how many electrical loads in East Kalimantan should be prepared by Indonesian’s State Electricity Company (PT PLN) in order to ensure comfortable for communities on religious holidays. Two sample religious holidays have been taken; Eid al-Fitr and Christmas Day, then the forecasting was carried out using SARIMA model on historical hourly data from 2015-2018. The result of this research shown that the best SARIMA model on Eid al-Fitr is SARIMA (0,2,1)(0,1,0)24 with 16,99% of MAPE and the best SARIMA model on Christmas Day is SARIMA (0,2,1)(0,1,0)24 with 8.68%.of MAPE.